The organization in inclusive companies - Méndez Bravo, Julio Cesar; Méndez Bravo, Manuel Alberto (Revista Universidad de Guayaquil, 2017)
The generation of inclusive companies grows. This is due to the vision of the conception of benefits that can be generated when developing businesses focused on the base of the pyramid. Not only the economic and fiscal benefits for entrepreneurs and their organizations, but also the social and economic benefits generated by this socio-economic sector. This makes the organizational approach of these companies more explicit and more detailed, given the human capital that is available in the organization, and must generate visionary managers, leaders and cooperatives.